Pictorial health warning labels on the waterpipe device are effective in reducing smoking satisfaction, puffing behaviour and exposure to CO: first evidence from a crossover clinical laboratory study. Issue Volume 28:Issue e1(2019) (11th January 2019) - Maziak, Wasim; Ben Taleb, Ziyad; Ebrahimi Kalan, Mohammad; Eissenberg, Thomas; Thrasher, James; Shihadeh, Alan; Asfar, Taghrid
Abstract : Objectives: This study examined the effect of pictorial health warning labels (HWLs) on the waterpipe (WP) device on smokers' experience, puffing behaviour, harm perception and exposure to respiratory toxicants. Methods: Thirty WP smokers completed two 45 min ad libitum smoking sessions (WP without HWL vs WP with HWL) in a crossover design study. Exhaled carbon monoxide (eCO) was measured before and after each smoking session. Puff topography was recorded throughout the smoking session, and participants completed survey questionnaires assessing subjective smoking experiences and harm perception. Results: Significant differences were observed in eCO levels between the two study conditions, with lower levels of eCO boost recorded following smoking the WP fitted with HWL (16 ppm) compared with WP without HWL (22.7 ppm). Participants had more puffs, shorter interpuff intervals and a higher total puff volume during smoking the WP without HWL relative to WP with HWL (p values <0.05). We documented enhanced reports of satisfaction, taste and puff liking following smoking the WP without HWL compared with the WP with HWL. WP harm perception was significantly higher among participants after smoking the WP with HWL compared with WP without HWL. Conclusion: This pilot study shows that placing HWL on the WP device is effective in reducing WP smoker's positive experiences, puffing parameters and exposure to carbon monoxide. HWLs lead also to more appreciation of WP harmful effects, making them a promising regulatory approach for addressing the spread of WP smoking among young adults in the USA.